ANALISIS PEMBERDAYAAN MASYARAKAT MELALUI KAMPUNG TEMATIK HOME INDUSTRY DI KELURAHAN KARANGANYAR GUNUNG KECAMATAN CANDISARI KOTA SEMARANG - Raura Farrah El Ha; Herbasuki Nurcahyanto; Aufarul Marom (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2022)
Law number 23 of 2014 provides for submission to local governments to take advantage of their potential in order to realize the welfare of their people. The Semarang City Government to increase economic growth, reduce poverty and unemployment has thematic village innovations as an effort to increase local potential, community empowerment, and settlement infrastructure. The purpose of this study is to analyze community empowerment through home industry thematic villages and the inhibiting factors. This research uses qualitative descriptive research. This research analyzes the stages of community empowerment through home industry thematic villages which consist of the awareness stage, the capacity stage, and the empowerment stage. The informant determination technique used in this research is snowball sampling with data collection methods through interviews, observation, and documentation. The results of the study show that community empowerment through home industry thematic villages has provided community understanding to map the potential and problems of the region even though it has not yet reached the level of empowerment and independence. The stages of community empowerment through home industry thematic villages have been in accordance with community empowerment both based on thematic village regulations and literature on community empowerment. The empowerment stage starts from the awareness stage, continues with the capacity stage and ends with the empowerment stage, but there are still some problems in each stage of the empowerment. Community empowerment through home industry thematic villages has inhibiting factors, including communication, resources, disposition, and bureaucratic structure. To overcome these problems, it is necessary to have regular monitoring and evaluation from the government to assist the implementation of community empowerment through home industry thematic villages so that problems and needs can be accommodated in accordance with the provisions of the Semarang mayor's regulation number 22 of 2018.